Genetic parameters for fertility and production traits in Red Angus cattle - Boldt, Ryan John, author; Enns, R. Mark, advisor; Speidel, Scott E., advisor; Koontz, Stephen, committee member (Colorado State University. Libraries, 2017)
To view the abstract, please see the full text of the document.
Keywords: genetic correlation; stayability; heifer pregnancy; beef cattle